Genetically Improved Abbassa Nile Tilapia (GIANT) strain Generation 18 data - Attia, Sameh; Mengistu, Samuel; Hamilton, Matthew (2024)
Identifiers, parents and spawning date for all families produced in the WorldFish G18 Abbassa Nile Tilapia (GIANT) strain.